A reflection on systems thinking as a research tool in sport and exercise science - Drust, B. (Journal of Sports Sciences, 2025)
Since completing my PhD in the physiology of football I have always been fascinated in trying to understand the performance limitations within the sport and how we can then subsequently design interventions to address these factors. Even as far back as 1997 I was aware that the science had demonstrated that performance in football was multifactorial though my training and thinking frameworks always led me to focus on the physiological.